Comportamientos de riesgo en los adolescentes madrileños - Meneses, Carmen (Miscelánea Comillas, 2008)
This study analyzes the risk behavior about violence, drug use, sexual behavior, road safety and eating disorders in a representative sample of 1,720 ESO Students from Madrid. The majority of adolescents are not engaged in the most important risk behaviors. However, 22% has taken part on a fight last year, 7.5% has been involved in a car or motorcycle accident, 20% was wearing the helmet on motorcycle and 4.7% was not using seatbelt on the travelling with friends. 10% indicated eating disorders. The most used drugs were tobacco, alcohol and cannabis and 28% had got drunk in the last year. 18% had had sexual intercourse and one of ten adolescents had had sexual relations without consent. There had been found important differences on the analyzed risk behaviors between sexes, grade/age and ethnic autoidentification. The Religious factor and Communication family factor were important for those students that have not taken risk behaviors.